Mortality risk factors and fulminant sub-phenotype in anaerobic bacteremia: a 10-year retrospective, multicenter, observational cohort study - Kentaro Nagaoka; N. Iwanaga; Y. Takegoshi; Y. Murai; H. Kawasuji; M. Miura; Y. Sato; Y. Hatakeyama; H. Ito; Y. Kato; N. Shibayama; Y. Terasaki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The oceanographic isolation of the Ogasawara Islands and genetic divergence in a reef‐building coral - Patricia H. Wepfer; Yuichi Nakajima; Atsushi Fujimura; Alexander S. Mikheyev; Evan P. Economo; Satoshi Mitarai (Journal of Biogeography, 2022)
Aim Due to their spatial isolation, oceanic islands are natural systems to study evolutionary divergence. The Ogasawara Islands belong to the most isolated archipelagos on Earth and are well‐known for their high terrestrial endemicity; however, less is known about the marine realm. Here, we analyse the degree of oceanographic isolation of the archipelago based on genetic data of a reef‐building coral and a biophysical dispersal model. Location North‐Western Pacific (Ogasawara, Ryukyu, Daito Islands, Guam). Taxon Galaxea fascicularis L. Method Three to 15 specimens were sampled at several sites in Ogasawara and its closest potential migration sources in southern Japan and the Mariana Islands (Guam) and RAD‐sequenced. 108 specimens from the common Pacific lineages ‘L’ (Ryukyu‐ and Daito Islands, Guam) and ‘Ogasawara’ (Ogasawara) were analysed with population genetics and demographic modelling . Oceanographic dispersal was investigated by inverse particle tracking using a Lagrangian particle advection simulation based on ROMS and applying biological dispersal parameters of G. fascicularis . Results The G. fascicularis population in Ogasawara is genetically highly differentiated from the next closest reefs in the region and has diverged from the Ryukyu Islands under very little, asymmetric, eastward migration. Inverse particle tracking confirmed the oceanographic isolation of Ogasawara and showed that the islands are rarely but most likely reached by settlers from the Ryukyu Islands by long‐distance‐dispersal of exceptionally long‐lived larvae (>44 days), with no dispersal vice versa. Main conclusions Ogasawara is a dispersal sink location and the high degree of genetic differentiation in Galaxea has resulted from strong oceanographic isolation. This research highlights how oceanographic features impact species‐level genetic differentiation even in well‐dispersed taxa such as broadcast‐spawning corals, and they are likely even more pronounced in less vagile organisms . These findings suggest the Ogasawaran Archipelago should be considered an important priority for marine conservation, alongside its high importance for terrestrial conservation.

Transplantation of Human-Induced Pluripotent Stem Cell-Derived Neural Precursors into Early-Stage Zebrafish Embryos - J. Strnadel; H. Wang; C. Carromeu; A. Miyanohara; K. Fujimura; E. Blahovcova; V. Nosal; H. Skovierova; R. Klemke; E. Halasova (Journal of Molecular Neuroscience, 2018)

Mechanisms of Cross-Shore Transport and Spatial Variability of Phytoplankton on a Rip-Channeled Beach - Atsushi G. Fujimura; Ad J. H. M. Reniers; Claire B. Paris; Alan L. Shanks; Jamie H. MacMahan; Steven G. Morgan (Frontiers in Marine Science, 2018)

Surf zones regulate larval supply and zooplankton subsidies to nearshore communities - Steven G. Morgan; Alan L. Shanks; Jamie MacMahan; Ad J. H. M. Reniers; Chris D. Griesemer; Marley Jarvis; Atsushi G. Fujimura (Limnology and Oceanography, 2017)
Surf zone hydrodynamics vary along shorelines potentially affecting the delivery of larvae and zooplankton subsidies to intertidal communities, and, hence, the intensity of postsettlement interactions, growth and reproduction of filter‐feeding foundation species and planktivorous fishes. We investigated the ability of zooplankton assemblages to enter the wide surf zone of the rip‐channeled, more dissipative beach at Sand City, California, and the narrow surf zone of the steep reflective beach at nearby Carmel River State Beach. Every day for a month, we surveyed zooplankton inside and outside the surf zone and concomitant larval settlement of the dominant invertebrate onshore at each site in this upwelling regime. At the more dissipative surf zone, all zooplankters were far more concentrated inside than outside the surf zone. Many taxa increased in the surf zone and the predominant invertebrate on beaches, Emerita analoga , settled abundantly when prevailing northwesterly winds relaxed and waves were small. At the reflective surf zone, concentrations of zooplankters of most taxa were far greater outside than inside the surf zone, and many taxa increased in the surf zone when waves were small. Twice as many taxa were positively correlated inside and outside the surf zone at the dissipative than the reflective surf zone, indicating that zooplankters were more freely exchanged although behavior also played a role. Thus, spatial and temporal variation in surf zone hydrodynamics may regulate subsidies of zooplankton food and larval recruits to nearshore communities with potential cascading effects on community dynamics and structure.

Numerical simulations of larval transport into a rip‐channeled surf zone - Atsushi G. Fujimura; Ad J. H. M. Reniers; Claire B. Paris; Alan L. Shanks; Jamie H. MacMahan; Steven G. Morgan (Limnology and Oceanography, 2014)
Competent larvae of intertidal invertebrates have to migrate toward shore for settlement; however, their migration through the surf zone is not understood. We investigated larval transport mechanisms at a rip‐channeled beach. Because tracking larvae in the surf zone is infeasible, we used a three‐dimensional biophysical model to simulate the processes. The coupled model consists of a physical module for currents and waves, and a biological module for adding larval traits and behaviors as well as Stokes drift to Lagrangian particles. Model calculations were performed with and without onshore wind forcing. Without wind, wave‐driven onshore streaming occurs in the bottom boundary layer outside the surf zone. With onshore wind, onshore currents occur near the surface. In the surf zone, offshore‐directed rip currents and compensating onshore‐directed currents over shoals are formed in both no‐wind and wind cases. In the biological module, neutral, negative, and positive buoyant particles were released offshore. Additionally, particles either sank in the presence of turbulence or not. Two scenarios achieved successful onshore migration: Negatively buoyant larvae without wind forcing sink in the turbulent bottom boundary layer and are carried onshore by streaming; positively buoyant larvae drift toward shore in wind‐driven surface currents to the surf zone, then sink in the turbulent surf zone and remain near the bottom while transported shoreward. In both cases, the larval concentration is highest in the rip channel, consistent with field data. This successful result is only obtained if turbulence‐dependent sinking behavior and Stokes drift are included in the transport of larvae.

Fine-scale features on the sea surface in SAR satellite imagery – Part 2: Numerical modeling - S. Matt; A. Fujimura; A. Soloviev; S. H. Rhee; R. Romeiser (Ocean Science, 2014)
With the advent of the new generation of synthetic aperture radar (SAR) satellites, it has become possible to resolve fine-scale features on the sea surface on the scale of meters. The proper identification of sea surface signatures in SAR imagery can be challenging, since some features may be due to atmospheric distortions (gravity waves, squall lines) or anthropogenic influences (slicks), and may not be related to dynamic processes in the upper ocean. In order to improve our understanding of the nature of fine-scale features on the sea surface and their signature in SAR, we have conducted high-resolution numerical simulations combining a three-dimensional non-hydrostatic computational fluid dynamics model with a radar imaging model. The surface velocity field from the hydrodynamic model is used as input to the radar imaging model. The combined approach reproduces the sea surface signatures in SAR of ship wakes, low-density plumes, and internal waves in a stratified environment. The numerical results are consistent with observations reported in a companion paper on in situ measurements during SAR satellite overpasses. Ocean surface and internal waves are also known to produce a measurable signal in the ocean magnetic field. This paper explores the use of computational fluid dynamics to investigate the magnetic signatures of oceanic processes. This potentially provides a link between SAR signatures of transient ocean dynamics and magnetic field fluctuations in the ocean. We suggest that combining SAR imagery with data from ocean magnetometers may be useful as an additional maritime sensing method. The new approach presented in this work can be extended to other dynamic processes in the upper ocean, including fronts and eddies, and can be a valuable tool for the interpretation of SAR images of the ocean surface.

Sialyl-glycoconjugates in cholesterol-rich microdomains of P388 cells are the triggers for apoptosis induced by Rana catesbeiana oocyte ribonuclease - Y. Ogawa; S. Sugawara; T. Tatsuta; M. Hosono; K. Nitta; Y. Fujii; H. Kobayashi; T. Fujimura; H. Taka; Y. Koide; I. Hasan; R. Matsumoto; et al. (Glycoconjugate Journal, 2014)

Biological and chemical characteristics of the coral gastric cavity - S. Agostini; Y. Suzuki; T. Higuchi; B. E. Casareto; K. Yoshinaga; Y. Nakano; H. Fujimura (Coral Reefs, 2012)

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate - P. Cuet; M. J. Atkinson; J. Blanchot; B. E. Casareto; E. Cordier; J. Falter; P. Frouin; H. Fujimura; C. Pierret; Y. Susuki; C. Tourrand (Coral Reefs, 2011)

Contamination and impacts of new antifouling biocide Irgarol-1051 on subtropical coral reef waters - M. A. Sheikh; T. Higuchi; H. Fujimura; T. S. Imo; T. Miyagi; T. Oomori (International Journal of Environmental Science and Technology, 2009)

Fine mapping of a strong QTL of field resistance against rice blast, Pikahei-1(t), from upland rice Kahei, utilizing a novel resistance evaluation system in the greenhouse - Xin Xu; H. Chen; T. Fujimura; S. Kawasaki (Theoretical and Applied Genetics, 2008)

Lunar-A mission: Outline and current status - H. Mizutani; A. Fujimura; S. Tanaka; H. Shiraishi; T. Nakjima (Journal of Earth System Science, 2005)

Positional cloning of the rice Rf-1 gene, a restorer of BT-type cytoplasmic male sterility that encodes a mitochondria-targeting PPR protein - H. Akagi; A. Nakamura; Y. Yokozeki-Misono; A. Inagaki; H. Takahashi; K. Mori; T. Fujimura (Theoretical and Applied Genetics, 2004)

Identification of two loci for resistance to clubroot (Plasmodiophora brassicae Woronin) in Brassica rapa L. - K. Suwabe; H. Tsukazaki; H. Iketani; K. Hatakeyama; M. Fujimura; T. Nunome; H. Fukuoka; S. Matsumoto; M. Hirai (Theoretical and Applied Genetics, 2003)

Mapping QTLs influencing rice floral morphology using recombinant inbred lines derived from a cross between Oryza sativa L. and Oryza rufipogon Griff. - Y. Uga; Y. Fukuta; H. W. Cai; H. Iwata; R. Ohsawa; H. Morishima; T. Fujimura (Theoretical and Applied Genetics, 2003)

Mapping QTLs influencing rice floral morphology using recombinant inbred lines derived from a cross between Oryza sativa L. and Oryza rufipogon Griff - Y. Uga; Y. Fukuta; H. W. Cai; H. Iwata; R. Ohsawa; H. Morishima; T. Fujimura (Theoretical and Applied Genetics, 2003)

Micron, a microsatellite-targeting transposable element in the rice genome - H. Akagi; Y. Yokozeki; A. Inagaki; K. Mori; T. Fujimura (Molecular Genetics and Genomics, 2001)

Highly polymorphic microsatellites of rice consist of AT repeats, and a classification of closely related cultivars with these microsatellite loci - H. Akagi; Y. Yokozeki; A. Inagaki; T. Fujimura (Theoretical and Applied Genetics, 1997)